2008
DOI: 10.1021/ar8000475
|View full text |Cite
|
Sign up to set email alerts
|

Peptide and Protein Mimetics Inhibiting Amyloid β-Peptide Aggregation

Abstract: Protein misfolding is related to some fatal diseases including Alzheimer's disease (AD). Amyloid beta-peptide (Abeta) generated from amyloid precursor protein can aggregate into amyloid fibrils, which are known to be a major component of Abeta deposits (senile plaques). The fibril formation of Abeta is typical of a nucleation-dependent process through self-recognition. Moreover, during fibrillization, several metastable intermediates such as soluble oligomers, including Abeta-derived diffusible ligands (ADDLs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
218
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(223 citation statements)
references
References 62 publications
4
218
0
1
Order By: Relevance
“…[22] In transgenic mouse models for AD and in human AD sufferers, 17-HSD10 has been shown to have increased expression levels and has gained considerable attention as a result of its ability to bind A, suppress A-induced apoptosis and free-radical generation in neurons. [11] It is known that the interaction between 17-HSD10 and A , A and A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) takes place in the nanomolar range (K d ~ 40-80 nM), [11] which agrees well with the low cellular concentrations of A peptide expected at the early stages of AD. In addition, mutagenesis and inhibition studies have suggested that the L D loop of 17-HSD10, comprising residues C91-D119, plays a critical role in A binding.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…[22] In transgenic mouse models for AD and in human AD sufferers, 17-HSD10 has been shown to have increased expression levels and has gained considerable attention as a result of its ability to bind A, suppress A-induced apoptosis and free-radical generation in neurons. [11] It is known that the interaction between 17-HSD10 and A , A and A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) takes place in the nanomolar range (K d ~ 40-80 nM), [11] which agrees well with the low cellular concentrations of A peptide expected at the early stages of AD. In addition, mutagenesis and inhibition studies have suggested that the L D loop of 17-HSD10, comprising residues C91-D119, plays a critical role in A binding.…”
Section: Introductionsupporting
confidence: 72%
“…However, a lack of -sheet structure at acidic pH cannot exclusively account for the observed lack of aggregation inhibition, as it has been shown that 17-HSD10 does not bind A (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), which is known to exhibit a -sheet conformation by CD and NMR studies. [63] In contrast, the conformation of the N-terminal region, residues 17-20 of A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) that constitute the binding interface with 17-HSD10, [11] is known to exhibit a random-coil/-helix/-sheet equilibrium that is highly dependent on pH conditions. [61,63,64] At pH 7-8, it has been demonstrated that residues 10-28, containing the putative 17-HSD10 binding interface, are in equilibrium between random coil and -helix conformations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our work is inspired by previous studies that demonstrated the ability of amyloidogenic peptide fragments to inhibit fibrillization of polypeptides containing the cognate peptide sequences (25)(26)(27)(28)(29)(30)(31). A common concern when using amyloidogenic peptides as aggregation inhibitors is their poor solubility.…”
Section: Discussionmentioning
confidence: 99%